Tribes of Asteraceae in Mexico, morphology and identification key - Redonda-Martínez, Rosario (Instituto de Ecología, A.C., 2022)
Background and Aims: The classification of Asteraceae has changed considerably in the last two decades due to the use of molecular tools and microcharacters that, when analyzed together with morphological data, have allowed not only to clarify phylogenetic relationships, but also to segregate and recognize new subfamilies and tribes. This work aims to present an identification key for the native and introduced tribes of Asteraceae in Mexico and to illustrate their main diagnostic characters. Methods: From a bibliographic review, the observation of the fresh and herborized material, the distinctive characteristics of the native and introduced tribes of Asteraceae found in Mexico were compiled. Using a stereoscopic microscope with an attached camera, the structures in which the main distinctive characteristics of each tribe can be seen were photographed. Key results: The essential characteristics to identify the 26 tribes of Asteraceae found in Mexico are in the heads, being the type of florets, the shape, orientation, and pubescence of the branches of the style, the shape of the apex, base, and the collar of the anther, shape of the cypselas, presence or absence of phytomelanin in the cypselas, as well the symmetry, persistence, and type of elements of the pappus. Conclusions: For the first time, the characteristics of the flower heads for the 26 tribes of Asteraceae distributed in Mexico are presented, in addition to the organs associated with them such as involucre, phyllaries, receptacle, paleas, peripheral florets, central florets, androecium, style, cypselas, and pappus. These structures are described in a simple way and illustrated with photographs of material in vivo, herbarium, or preserved in spirit, highlighting the diagnostic characters of each tribe, the most common morphology, as well as the exceptions that occur in some of its members.